The impact of traditional birth attendants on maternal and child health in Ikole LGA of Ekiti State, Nigeria (2013)
"Traditional Birth Attendants have been assisting the pregnant women and children mostly in the rural 14 areas. This study intended to explore the impact of traditional birth attendants on maternal and child health in Ikole LGA 15 of Ekiti State, Nigeria. The study adopted the use of functionalist theory and Social Action theory in explaining the impact of TBAs on maternal and child health and the factors influencing the utilization of TBAs facilities respectively. A descriptive research design was employed for the study, using both quantitative and qualitative methods of data collection. The sample size was selected through random sampling technique and a total of 250 questionnaires were distributed to the pregnant women and mothers with children ≤ 5 years old, who were currently attending antenatal and/or postnatal with TBAs and were resident in the Ikole Local Government Area. Findings revealed that 90.4% of the pregnant women and nursing mothers had exclusively utilized TBAs facility. Also, majority of the respondents believed that TBAs have helped them solved their health problems and ensured safe delivery. Consequently, the outcome of the study indicates that some women resort to TBAs assistance because they believe in the efficacy of the TBAs especially for spiritual assistance. Generally, the TBAs should be given more training to be aware that they are not “illegal,” so that their work does not go underground and becomes dangerous. There should be an integration of TBAs and the health centers as it is practiced in China to deal with the spiritual aspect of health care delivery which makes many people patronize TBAs. "